4*(0,6x-0,3)-3*(0,7x-0,1)=0

Simple and best practice solution for 4*(0,6x-0,3)-3*(0,7x-0,1)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4*(0,6x-0,3)-3*(0,7x-0,1)=0 equation:


4*(0,6x-0,3)-3*(0,7x-0,1)=0

We simplify the equation to the form, which is simple to understand
4*(0,6x-0,3)-3*(0,7x-0,1)=0

Reorder the terms in parentheses
+(+2.4x-1.2)-3*(0,7x-0,1)=0

Remove unnecessary parentheses
+2.4x-1.2-3+*(,7x-0,1+)=0

Reorder the terms in parentheses
+2.4x-1.2+(-2.1x + 0.3)=0

Remove unnecessary parentheses
+2.4x-1.2-2.1x + 0.3=0

We move all terms containing x to the left and all other terms to the right.
+2.4x-2.1x=0+1.2-0.3

We simplify left and right side of the equation.
+ 0.3x=0.9

We divide both sides of the equation by 0.3 to get x.
x=3

See similar equations:

| [2x-1]=2 | | -6x-3(7x-26)=-11 | | 14u-8+6u+41= | | -288=2x-6(6x-20) | | 4(4x+1)+4x(-2)= | | .5(4x-2)=x+5 | | 2x^4-x^3+2x^2-1=0 | | (3h-2m)(2h+m)= | | 2.3-r=10.4 | | a+.11=.20 | | a+.11=.290 | | 7/8-1/4-2/4-(1/2)^2 | | w^2+45+18w=0 | | 3*(x-7)-(9-2x)=2*(12-x)-(x-10) | | 54x^2-5x-325=0 | | x^2-3x=60 | | (11.7*10*12)/(5.2*10*5) | | 1.2x2/3 | | 5r+7-3r=-3 | | x+y-z=11 | | (2.1*7.5)+(2.1*1.8)= | | x+(x-73)+67=180 | | 3(1j+4)=-2j+1j | | 0.19x=53.20 | | x+6y-5z=-7 | | (4x+20)+(5x-2)=180 | | -240=5x-3(-5x+20) | | x+30=5x+10 | | 2x^2+5x+108=0 | | (5x-8)=4 | | 5*3b-4b=11 | | 7c+5=(3c-4) |

Equations solver categories